Analysis Of the Symbolic Convergence of Activism with the Hashtag #PercumaLaporPolisi on Twitter Social Media as A Virtual Public Space - Akhmad Ridha Djamaluddin; Sri Hastjarjo; Ignatius Agung Satyawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The hashtag #PercumaLaporPolisi (which means it is useless to report to the police) emerged after a flurry of alleged child rape by his biological father in East Luwu, South Sulawesi, was halted by local police. This issue was then widely discussed, went viral on social media, and drew protests from netizens through the hashtag #PercumaLaporPolisi. This study aims to analyze the symbolic convergence that occurs on Twitter social media through conversations between Twitter account users in the use of hashtags or hashtag activism #PercumaLaporPolisi in the context of Twitter as a virtual public space. This qualitative research uses descriptive analysis techniques based on case studies that collect and record data from the field through hashtag analysis on Twitter in the hashtag period from October 6, 2021, to December 7, 2021. The data obtained will then be analyzed based on Bormann’s Symbolic Convergence theory. The results showed that hashtag activism #PercumaLaporPolisi is a form of symbolic convergence that occurs on social media as a public sphere. It was initiated by the spread of symbols in the form of messages by @projectm_org accounts through his tweets on Twitter which ultimately formed a fantasy chain based on the theme of fantasy of disappointment to police officers over rape cases handled unfairly and inappropriately.